Effect of high methoxyl pectin on pea protein in aqueous solution and at oil/water interface - Gharsallaoui, Adem; Yamauchi, Kosuke; Chambin, Odile; Cases, Eliane; Saurel, Rémi (Carbohydrate Polymers, 2010)
The effect of the addition of high methoxyl pectin on the stability of pea protein isolate emulsions was investigated. Except for low pectin concentrations at acidic pHs where bridging flocculation occurred the addition of pectin improved emulsion stability to pH changes and depletion flocculation induced by maltodextrin addition. The mechanism of pectin induced stability was probed by measuring protein–pectin complex formation in solution, zeta potential of the emulsions droplets and the change in surface viscoelasticity on pectin addition. The phase diagrams of pectin–pea protein isolate in solution and pectin–pea protein-stabilized emulsions were established based on the obtained experimental results. These diagrams showed that under acidic conditions and at low pectin concentrations, electrostatic bridging phenomena leads to the formation of high size pectin–protein complexes causing an increase in turbidity in solution and oil droplet flocculation in emulsions. It was concluded that the pectin induced stability could be mainly assigned to steric repulsion and oil–water interfacial membrane rigidity improvement after pectin adsorption. In fact, the emulsions formed after pectin adsorption could consist of oil droplets surrounded by multilayer interfacial coatings, which are comprised of an inner interfacial protein film and an outer pectin layer.